Development and quality evaluation of deep fried carrot chips during storage - Ganai, Shaiq Ahmad; Kounsar, Rifat Kounsar; Gani, Murtaza; Dar, Aamir Hussain; Allali , Farhana (Journal of Postharvest Technology, 2019)
The objective of this study was to develop and evaluate the properties of deep fried carrot chips during storage. The carrot slices were blanched at 80°C for 4 min. followed by pre-treatments with NaCl (2%):T1, CaCl2 (2%):T2, KMS (0.15%):T3 and KMS (0.15%) + CaCl2 (2%):T4, and then partially dried at 60°C for 2 hr, fried and compared with control samples. The storage depicted significant increase in mean moisture content while there was a decreasing trend in the mean values of ash, protein, fat and ascorbic acid contents. The storage depicted the gradual decrease in the mean β-carotene values from 43.98 to 41.64 (mg/100g). The maximum retention of β-carotene was noticed in T4 (43.65) while the minimum in T0 (42.12). The color (L*, a*, b*) values of stored carrot chips showed a progressive decrease in all the treatments with maximum change noticed in T0. The organoleptic evaluation showed that scores for color, taste, appearance and overall acceptability were highest for T4, whereas the scores of crispness were highest in T3.